Aicardi–Goutières syndrome with SAMHD1 deficiency can be diagnosed by unscheduled DNA synthesis test - Senju, Chikako; Nakazawa, Yuka; Shimada, Mayuko; Iwata, Dai; Matsuse, Michiko; Tanaka, Katsumi; Miyazaki, Yasushi; Moriwaki, Shinichi; Mitsutake, Norisato; Ogi, Tomoo (Frontiers in Pediatrics, 2022)
Aicardi–Goutières-syndrome (AGS) is a rare genetic disorder characterised by progressive encephalopathy, involving microcephaly, intracranial calcification, and cerebrospinal fluid lymphocytosis with increased interferon-α concentrations. The clinical features of AGS overlap with fetal cerebral anomalies caused by congenital infections, such as TORCH (toxoplasmosis, other, rubella, cytomegalovirus, and herpes), or with those of other genetic-disorders showing neonatal microcephaly, including Cockayne syndrome (CS) with transcription-coupled DNA repair deficiency, and Seckel syndrome showing aberrant cell-cycle checkpoint-signaling. Therefore, a differential diagnosis to confirm the genetic cause or a proof of infection should be considered. In this report, we describe an individual who showed primordial dwarfism and encephalopathy, and whose initial diagnosis was CS. First, we conducted conventional DNA-repair proficiency tests for the patient derived fibroblast cells. Transcription-coupled nucleotide-excision-repair (TC-NER) activity, which is mostly compromised in CS cases, was slightly reduced in the patient’s cells. However, unscheduled DNA synthesis (UDS) was significantly diminished. These cellular traits were inconsistent with the diagnosis of CS. We further performed whole exome sequencing for the case and identified a compound heterozygous loss-of-function variants in the SAMHD1 gene, mutations in which are known to cause AGS. As SAMHD1 encodes deoxyribonucleoside triphosphate triphosphohydrolase, we reasoned that the deoxyribonucleoside triphosphate (dNTP) pool size in the patient’s cells was elevated, and the labeling efficiency of UDS-test was hindered due to the reduced concentration of phosphorylated ethynyl-deoxyuridine (EdU), a nucleoside analogue used for the assay. In conclusion, UDS assay may be a useful diagnostic tool to distinguish between AGS with SAMHD1 mutations and other related diseases.